From micro culture of learning to regional needs: development of international social entrepreneurship course - Heidi Myyryläinen; Wilfred Ledoux Tchasse Simo (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
Social entrepreneurship education has grown an interest in the field of higher education (Howorth, Smith, and Parkinson, 2012; Mueller, Brahm, and Neck, 2015). Entrepreneurship education on social enterprises includes the same dilemmas as entrepreneurship education in general, but it also entails definitional choices on how social enterprises and social entrepreneurship are viewed. Entrepreneurship educators advocate experiential learning, and the course described here builds on experiential elements. This paper describes an aligned social entrepreneurship course organised by five higher education institutions. The course builds social entrepreneurship learning experience on three main dimensions: reflexive learning with international peer learners, using theoretical perspectives of social enterprises; social entrepreneurship and business models as a source for constructing new ideas, and grounding learning to a regional context by studying in a region and interacting with a locally rooted social entrepreneur.